Variação de alguns elementos micrometeorológicos no dossel de plantas de batata - Tazzo, Ivonete Fátima (2005)
Potato (Solanum tuberosum) crop has many cultivation problems such as pests and the diseases, that settle down in the plants if the environmental donditions are favorable. The more important meteorological elements for infection caused by patógenos are temperature and air humidity. The variation of some micrometeorological elements (the transmitance to the global solar radiation, temperature and air humidity) of a potato canopy, Macaca cv was determined. Two experiments were carried out, the first in the spring, from 15/10 to 05/12/2003, in the county of Silveira Martins, RS and the second in the autumn, from 27/03 to 08/06/2004, in the experimental area of the Crop Production Department of the Universidade Federal de Santa Maria, RS. A tower with five heights of continuous psicrometric measurements was installed for the temperature and air humidity measurements with three replications installed at middle canopy and at 1,0m above the soil. Each psicrometric couple consisted of two thermometers of electric resistance of platinum (Pt-100), installed inside of a micro-shelter. The incident solar radiation below of canopy was also measured, with a solarimeter tube, and in 2004, the radiation balance above the canopy, using two replications. The sensors were plugged to a datalogger, being continually stored the averages of periods of 10 minutes. The hourly values of the wind speed was measured at 2,0m above the soil, precipitation and flux density of the incoming solar radiation were determined using an automatic weather station. Phenometric evaluations consisted of the determinations of the leaf area index and height of the plants. The transmitance can be described by a negative exponential as a function of leaf area index and days after the transplant, and the transmitance tends to be larger in periods with precipitation. The largest values of daily maximum temperature generally happened in the middle or at the top of the canopy and the smallest values happened above 1,0m height, except for the days with North wind, when thermal profiles tend to invert. In the period of highest air heating during the day and in the moment of the maximum temperature, the more accentuated gradients of the air temperature occurred during clear days and with low wind speed. The daily minimum temperatures on the average were larger at about 0,5m above the canopy and smaller in the middle canopy, except under conditions of cloudy sky, with or without rain. The air temperature and the dew point air temperature, as well as its gradients, were larger during daytime than during nighttime. The daily maximum and minimum values of the relative air humidity and the dew point temperature of the air decreased gradually from near the soil surface, inside of the canopy to about 2,0m of height, with the smaller vertical gradient in days of calm winds, with cloudy sky and in the rain periods. Strong and moderate winds had little effect in the attenuation of the gradient of the air temperature during the day, although they significantly attenuated the gradient of the dew point temperature of the air during the cooling period of night, including in the hour of the minimum temperature.